Power analysis attack against encryption devices: a comprehensive analysis of AES, DES, and BC3 - Septafiansyah Dwi Putra; Mario Yudhiprawira; Sarwono Sutikno; Yusuf Kurniawan; Adang Suwandi Ahmad (Universitas Ahmad Dahlan, 2019)
Cryptography is a science of creating a secret message and it is constantly developed. The development consists of attacking and defending the cryptography itself. Power analysis is one of many Side-Channel Analysis (SCA) attack techniques. Power analysis is an attacking technique that uses the information of a cryptographic hardware’s power consumption. Power analysis is carried on by utilizing side-channel information to a vulnerability in a cryptographic algorithm. Power analysis also uses a mathematical model to recover the secret key of the cryptographic device. This research uses design research methodology as a research framework started from research clarification to descriptive study. In this research, power analysis attack is implemented to three symmetrical cryptographic algorithms: DES (Data Encryption Standard), AES (Advanced Encryption Standard), and BC3 (Block Cipher 3). The attack has successfully recovered 100% of AES secret key by using 500 traces and 75% DES secret key by using 320 traces. The research concludes that the power analysis attack using Pearson Correlation Coefficient (PCC) method produces more optimal result compared to a difference of means method.